Growth inhibition of rhizobia isolated from arctic legumes (Astragalus and Oxytropis spp.) and sainfoin (Onobrychis viciifolia) by sainfoin seed diffusates - Prévost, D.; Jain, D.K.; Bordeleau, L.M. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1990)
Cold-adapted arctic rhizobia (from Astragalus and Oxytropis species) were used in nodulation studies and field inoculation trials with a temperate forage legume, sainfoin (Onobrychis viciifolia), since they have the potential to improve symbiotic nitrogen fixation at low temperatures. A major concern in legume inoculation is the toxicity of seed and root tannins to rhizobia. We studied the effects of sainfoin seed diffusates on the growth of 47 arctic and 2 sainfoin strains of rhizobia. Growth of all tested strains on yeast-extract mannitol agar plate was inhibited to various degrees by sainfoin seed diffusates. There was no correlation between the zone of inhibition and the symbiotic effectiveness of each strain on sainfoin. However, growth inhibition was totally reversed by the addition of iron as Fe-EDTA in the agar medium. In liquid medium without iron, growth inhibition of an arctic strain was 94% after 4-day growth. With the addition of 100 µM Fe-EDTA, inhibition was only 5%, and with 100 µM Fe-citrate, 76 %. These results underline the importance of evaluating the toxicity effect under normal rhizospheric conditions.